Geriatric Dentistry in the opinion of students from Poznan University of Medical Sciences - Koczorowski, Ryszard; Gałczyńska-Rusin, Małgorzata; Hemerling-Powidzka, Monika (Journal of Stomatology, 2015)
Introduction. Poznan University of Medical Sciences is the first Polish medical school with a department focused on interdisciplinary treatment of elderly patients providing undergraduate training in geriatric dentistry. Aim of the study. To evaluate the quality of geriatric dentistry training on the basis of a questionnaire, designed by the authors, that was completed by fifth-year students upon finishing their clinical activities. Material and methods. The study comprised 309 questionnaires, collected after the completion of a two-week course, from 195 Polish- and 114 English-speaking students in the academic years 2010/2011 and 2011/2012. The course followed a training program prepared at the Geriatric Dentistry Clinic, which was based on course books (in Polish and English) authored by the head of this clinic. Results. In the opinion of all those surveyed, the course comprising theoretical and practical parts was interesting and improved their treatment skills as well as their approach to elderly patients. The majority of students stated that considering the broad range of subjects covered (social, psychological and systemic issues together with various aspects of dentistry), the 30-hour duration of the course was not sufficient. The assessment of the training content and its performance produced similar results in the Polish- and English-speaking groups of students. Conclusions. Questionnaires evaluating undergraduate training programs may be a helpful tool in an effort to improve the quality of education and may offer a valuable source of information to the teaching staff. Due to the increasing number of senior citizens and the complexity of treatment in that age group, it appears necessary to extend the time dedicated to instruction in the field of geriatric dentistry.